Plants Assemble Species Specific Bacterial Communities from Common Core Taxa in Three Arcto-Alpine Climate Zones - Kumar, Manoj; Brader, Günter; Sessitsch, Angela; Mäki, Anita; van Elsas, Jan D.; Nissinen, Riitta (Frontiers in Microbiology, 2017)
Evidence for the pivotal role of plant-associated bacteria to plant health and productivity has accumulated rapidly in the last years. However, key questions related to what drives plant bacteriomes remain unanswered, among which is the impact of climate zones on plant-associated microbiota. This is particularly true for wild plants in arcto-alpine biomes. Here, we hypothesized that the bacterial communities associated with pioneer plants in these regions have major roles in plant health support, and this is reflected in the formation of climate and host plant specific endophytic communities. We thus compared the bacteriomes associated with the native perennial plants Oxyria digyna and Saxifraga oppositifolia in three arcto-alpine regions (alpine, low Arctic and high Arctic) with those in the corresponding bulk soils. As expected, the bulk soil bacterial communities in the three regions were significantly different. The relative abundances of Proteobacteria decreased progressively from the alpine to the high-arctic soils, whereas those of Actinobacteria increased. The candidate division AD3 and Acidobacteria abounded in the low Arctic soils. Furthermore, plant species and geographic region were the major determinants of the structures of the endophere communities. The plants in the alpine region had higher relative abundances of Proteobacteria, while plants from the low- and high-arctic regions were dominated by Firmicutes. A highly-conserved shared set of ubiquitous bacterial taxa (core bacteriome) was found to occur in the two plant species. Burkholderiales, Actinomycetales and Rhizobiales were the main taxa in this core, and they were also the main contributors to the differences in the endosphere bacterial community structures across compartments as well as regions. We postulate that the composition of this core is driven by selection by the two plants.